Planned City Extensions analysis of historical - UN HABITAT (Nairobi UN HABITAT)
Developing countries are urbanizing at an incredibly fast pace and, in many cases, with unplanned settlements that pose enormous challenges. Growing cities need to define the urban planning frameworks that will guide the construction of new neighbourhoods and city extensions.
Keywords: Urbanization